Folin-Ciocalteu Reaction Alternatives for Higher Polyphenol Quantitation in Colombian Passion Fruits - Juan C. Carmona-Hernandez; Gonzalo Taborda-Ocampo; Clara H. González-Correa (International Journal of Food Science)
Passiflora edulis Flavicarpa, Passiflora edulis Sims, and Passiflora ligularis Juss are Colombian fruits (passion fruits) of important exportation value. They act efficiently as antioxidants, antifungal, and antimicrobial compounds due to their high polyphenol content. Polyphenols can be quantified by the Folin-Ciocalteu (F-C) reaction. Food matrices, solvent polarity, and several different reacting conditions are critical for the optimum extraction and quantification of polyphenols. Chromatographic identification and quantitation are satisfactory with access to a vast number of reference standards considering the availability of abundant phenolic compounds in crude extracts. The purpose of this study was to evaluate alternatives and specific F-C reacting conditions aiming at determining the highest total phenolic content (TPC) in three Colombian Passifloras. Among optimum reacting conditions, reduced reaction time and diluted alkali conditions yielded desirable positive results highlighting lower working time and minimum reagent waste production. For higher extraction yield, acetone 70% was the best solvent to capture more phenolics from the seedless pulp of these Colombian passion fruits.